2001
DOI: 10.1074/jbc.m009821200
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Rac-1, SEK-1/MKK-4, and Protein Kinase Cδ Is Required for Interleukin-6-induced STAT3 Ser-727 Phosphorylation and Transactivation

Abstract: Signal transducers and activators of transcription (STATs) 1 belong to a family of transcription factors that are activated in response to a variety of cytokines and growth factors (1-4). So far, seven different STATs have been identified in mammals; these STATs contain conserved DNA binding and Src homology 2 domains that include a C-terminal tyrosine phosphorylation site (4). Binding of cytokines to their corresponding receptors induces Jak kinase activity, which results in phosphorylation of STATs on a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 36 publications
(42 reference statements)
3
66
1
Order By: Relevance
“…An extensive search for known potential kinases inducing Ser-727 phosphorylation of STAT3 in response to IL-6 was performed by using inhibitors to PKCδ, ERK, JNK, p38 MAPK and mTOR (data not shown), as they have previously been described to induce this phosphorylation [18][19][20][21][22]. Our study revealed PKCδ as the main target molecule.…”
Section: Inhibition Of Pkcδ With Rottlerin Inhibits Stat3 Signallingmentioning
confidence: 66%
See 4 more Smart Citations
“…An extensive search for known potential kinases inducing Ser-727 phosphorylation of STAT3 in response to IL-6 was performed by using inhibitors to PKCδ, ERK, JNK, p38 MAPK and mTOR (data not shown), as they have previously been described to induce this phosphorylation [18][19][20][21][22]. Our study revealed PKCδ as the main target molecule.…”
Section: Inhibition Of Pkcδ With Rottlerin Inhibits Stat3 Signallingmentioning
confidence: 66%
“…In this study, we further characterised Ser-727 phosphorylation of STAT3 by IL-6 and its potential role in mouse 3T3-L1 adipocytes by using specific inhibitors for the kinase pathways presented above [18][19][20][21][22]. We concluded that PKCδ was not only important for Ser-727 phosphorylation, but also for the Tyr-705 phosphorylation, nuclear translocation and transcriptional properties of STAT3.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations